Severe dengue with acute abdomen- A diagnosis dilemma - Azizul Fadzli, Wan Jusoh@Ab Rahim; Nik Ahmad Shaiffudin, Nik Him; Abdul Hafiz, Shaharudin; Muhamad Hafiq, Ab Hamid (2019)
Dengue is an emerging mosquito-borne viral infection transmitted between humans by Aedes spp. The rapid growth of dengue cases globally created a public health challenge in managing it. Since the dengue is a viral disease, a patient usually presented with non- specific clinical features with no definite drug or vaccine proven to treat it. Hence, a simple diagnostic tool for the early phase of the illness, early supportive treatment and efficient vector control measures are the essential elements in a holistic approach to managing a dengue infection. However, with a non-specific presentation of the disease and high variability of rapid diagnostic test sensitivity and specificity, the diagnosis is more challenging. The failure of detecting dengue infection, especially the severe variety may lead to a grave consequence. This case illustrates how a non- specific presentation with false negative diagnostic test result leads to unnecessary surgical intervention in a severe dengue patient.